Creative expression, community, and calculated risks : protective and risk factors associated with BMX - Dave Camilleri; Shanee Katz (International Journal of Emotional Education)
This study explores the role of Bicycle Motocross (BMX) beyond its conventional recreational function, focusing on its impact on individual and social wellbeing. Through a quantitative approach employing the Adolescent Resilience Questionnaire and a tailored BMX Riding Experiences Survey, factors associated to BMX are used to predict mental and social health in riders ages 15 years to 55 years old (n=240) using linear regression analysis. The individual wellbeing dimensions investigated include confidence, emotional insight, negative cognition, social skills, and empathy. Additionally, social wellbeing aspects such as family, school, and peer connectedness are examined. Findings indicate that peer encouragement, family support, helping others after falls, creative opportunities, observational learning, and contributing to local riding spots emerged as significant positive predictors of overall wellbeing. Additionally, problem-solving demands and embracing managed risks in BMX correlated with reduced anxious thinking patterns. This research underscores the significance of BMX not merely as a recreational activity but as a promoter of comprehensive wellbeing across multiple domains.